2016
DOI: 10.1111/tbed.12585
|View full text |Cite
|
Sign up to set email alerts
|

Different Lineage of Porcine Deltacoronavirus in Thailand, Vietnam and Lao PDR in 2015

Abstract: Porcine deltacoronavirus (PDCoV) was detected by RT-PCR in 12 of 97 (12.4%) intestinal samples collected during 2015 from piglets with diarrhoea in Thailand, Vietnam and Lao PDR. Spike, membrane and nucleocapsid genes were characterized, and phylogenetic analyses demonstrated that PDCoV isolates from Thai and Lao PDR form a novel cluster, separated from US and China isolates, but relatively were more closely related to China PDCoV than US isolates. Vietnam PDCoVs, however, were grouped together with US PDCoV. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
81
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(85 citation statements)
references
References 17 publications
2
81
0
Order By: Relevance
“…Many types of viruses cause diarrhoea in animals, including TGEV (Zhang, Zhu, Zhu, Chen et al., ), swine enteric coronaviruses (SeCoVs) (Belsham et al., ), PEDV (Lohse et al., ; Tian et al., ; Zhang, Tian et al., ), porcine deltacoronavirus (Lee et al., ; Mai et al., ; Saeng‐Chuto et al., ) and rotaviruses (Kim et al., ). Rotaviruses cause acute dehydrating diarrhoea in various hosts, including children and young animals (Jiang, Liu, & Tan, ).…”
Section: Discussionmentioning
confidence: 99%
“…Many types of viruses cause diarrhoea in animals, including TGEV (Zhang, Zhu, Zhu, Chen et al., ), swine enteric coronaviruses (SeCoVs) (Belsham et al., ), PEDV (Lohse et al., ; Tian et al., ; Zhang, Tian et al., ), porcine deltacoronavirus (Lee et al., ; Mai et al., ; Saeng‐Chuto et al., ) and rotaviruses (Kim et al., ). Rotaviruses cause acute dehydrating diarrhoea in various hosts, including children and young animals (Jiang, Liu, & Tan, ).…”
Section: Discussionmentioning
confidence: 99%
“…Compare to the complete genome of another two common swine enteropathogenic coronaviruses (PEDV, TGEV), the PDCoV CHN-GD-2016 strain (GenBank no: MF280390) shares 43.39%, 42.79% nucleotide identity with PEDV GDS01 (GenBank no: KM089829.1) and TGEV AHHF (GenBank no: KX499468.1), respectively. Since it was first detected in 2012 in Hong Kong during a molecular epidemiology study of CoVs (Woo et al, 2012), PDCoV subsequently had been reported in at least 9 states of the United States, Thailand, Vietnam, Lao PDR, South Korea, Canada, and mainland China (Leyi et al, 2014;Marthaler et al, 2014;Saeng-Chuto et al, 2017;Sunhee Lee, 2014;Wang et al, 2014;Xu et al, 2018). These molecular surveillance studies indicated that PDCoV was a common viral pathogen of pigs around the world.…”
Section: Introductionmentioning
confidence: 99%
“…PDCoV was first reported in 2012 in Hong Kong during an epidemiological investigation conducted to identify new coronaviruses existing in nature (Woo et al, ). In early 2014, there was a reported PDCoV outbreak in the pig farms in the United States (Chen et al, ; Wang, Byrum, & Zhang, ), followed by subsequent outbreaks in Canada (Ojkic et al, ), South Korea (Lee et al, ), Thailand (Janetanakit et al, ; Saeng‐chuto et al, ) and mainland China (Dong et al, ), exhibiting a global distribution trend. Additionally, clinical reports have indicated that PDCoV exhibits enteropathogenicity, causing severe diarrhoea and vomiting in roughly 5‐ to 10‐day‐old gnotobiotic and conventional piglets (Chen et al, ; Jung et al, ).…”
Section: Introductionmentioning
confidence: 99%